CONCEPTION RATE DAN SERVICE PER CONCEPTION PADA SAPI PERANAKAN LIMOUSIN DAN SAPI PERANAKAN ONGOLE HASIL IB DI KECAMATAN PILANGKENCENG KABUPATEN MADIUN - Bhaskara, Alfiutha Propha; Suprayogi, Tri Wahyu; Darsono, Roesno; Srianto, Pudji; Hariadi, Mas'ud; Sardjito, Trilas (Ovozoa: Journal of Animal Reproduction, 2018)
The study was conducted to know conception rate and service per conception of Limousin Cross breed and Ongole Cross Breed in Pilangkenceng, Madiun. Data were collected for the periode of Oktober 2016 to February 2017 from inseminators in Pilangkenceng district. The data were taken by primary and secondary. Primary data retrieval were done by direct observation, which includes several variables, where the variables include: the identity of the breeder, feeding and drinking. The secondary data were obtained by recording the farmer's artificial insemination card. All data was analyzed to find a percentage of conception rate (CR) and find number of service per conception (S/C). Then S/C were analyzed with T-test adn CR were analyzed with chi-square test. The results of this research showed that the service per conception's average of limousin cross breed and ongole cross breed is 1,61 and 1,72. The average of conception rate limousin cross breed and ongole cross breed is 53% % and 59 %. The result showed no significant difference (p>0,05) on CR and S/C between limousin cross breed and ongole cross breed. The conclusion of this research showed that service per conception and conception rate of ongole cross breed in Pilengkenceng Madiun is better than limousin cross breed but there's no significant difference (p>0,05).